REPRODUCTIVE ATTITUDES AMONG STUDENTS (ACCORDING TO THE DATA OF SOCIOLOGICAL SURVEY) - Alexandr N. Suchkov (Высшее образование в России, 2016)
The study of reproductive behavior is one of the most important subjects of demographic research. Research of reproductive intentions most often is performed among young people: young families and students. The paper gives the results of sociological survey conducted by the author among the students of Moscow State University. Average values of children among students higher than average values of children among all population. Also, higher values of children are observed among a part of students, who are married or planning to get married atan early age, and a part of students who have three or more children in parent families. Also regularities of employment and evaluation of the demographic situation in the country with values of children are traced. The obtained results correlate with the results of similar sociological surveys among students.